2020
DOI: 10.5713/ajas.19.0619
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis of linear udder type traits and their relationship with milk yield and composition in indigenous Sahiwal cattle

Abstract: Objective: The present study was aimed at (i) reduction in dimensionality using principal component analysis of 17 linear udder type traits to define those components which best represent udder and teat conformation of Indian Sahiwal cattle and (ii) to identify those components having strongest relationship with milk production traits in Sahiwal cattle. Methods: The Principal Component Analysis (PCA) included 17 linear udder type traits using the correlation matrix between the traits to ensure that all traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…Table 5, shows the extent of the contribution of principal component analysis (PC 1 or PC 2 ) in the variance of the traits under this study; indicating that PC 1 contributes a greater amount of the variance of CI traits reached on 0.371. While it does not contribute badly to the contrast of LP and NSPC traits, In addition to PC 1 contributes a moderate amount to the total milk yield = 0.273, also., the PC2 for TMY=0.213, while DO = -0.004 for PC 1 and PC 2 = 0.949, this study agrees by Eyduran et al, (2013), Rebeka et al (2020) and Sinha et al (2021). 4.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 90%
See 1 more Smart Citation
“…Table 5, shows the extent of the contribution of principal component analysis (PC 1 or PC 2 ) in the variance of the traits under this study; indicating that PC 1 contributes a greater amount of the variance of CI traits reached on 0.371. While it does not contribute badly to the contrast of LP and NSPC traits, In addition to PC 1 contributes a moderate amount to the total milk yield = 0.273, also., the PC2 for TMY=0.213, while DO = -0.004 for PC 1 and PC 2 = 0.949, this study agrees by Eyduran et al, (2013), Rebeka et al (2020) and Sinha et al (2021). 4.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 90%
“…Estimates breeding values(EBV) of TMY, LP, CI, NSPC, and DO in Holstein cattle cows and the general mean value of Kaiser-Meyer Olkin (KMO) measures of sampling adequacy was obtained as 0.674, Chi-Square was 590.086, this indicated that the suitability of the data for PCA. The same model was reported by several authors Eyduran et al (2013) and Sinha et al (2021) with different cattle and observed that KMO measure of sampling adequacy were 0.867; 0.692 and 0.669, respectively.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 82%
“…While, the second component weights varied from -0.072 to 0.892 for DO and CI, respectively. The same trend found that by Campos et al, (2015) and Sinha et al, (2020). Prediction of TMY using production and reproduction traits Multiple regression analysis VIF values greater than 3, VIF were 47.6, 57.6, 48.9 and 1.2 for LP, CI, and DP and DO; respectively.…”
Section: Figure 1 Eigenvalues and Cumulative Percent Of Variance Witsupporting
confidence: 70%
“…They found that the single trait, single record model and the simple repeatability model were not appropriate in predicting breeding values at mature ages for rear udder width and rear udder height. More recently, Sinha et al [20] used principal component analysis to investigate 17 linear udder type traits representing udder and teat conformation and to identify those components having strongest relationship with milk production traits. Correspondingly, Soeharsono et al [21] predicted daily milk production based on linear body and udder morphometry of Holstein Friesian (HF) dairy cows.…”
Section: Introductionmentioning
confidence: 99%